INCREASING TEAMWORK OF ELEMENTARY SCHOOL STUDENTS THROUGH A PUZZLE ESTAFET GAME - Feti Astuti; Izzaty, Rita Eka; Saloh, Amerta Enun; Ayun, Mila Hita; Patrihartati, Sirka (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
Teamwork skills are essential for every student at the elementary school level. Teamwork teaches students to understand, feel, and implement group activities to achieve a common goal. The study aimed to increase student teamwork through a puzzle estafet game. This quantitative study has a pre-experimental research design and a one-group pretest and posttest design. Researchers used the entire population as a research sample, namely 25 fifth-grade students. Data collection used a questionnaire that was printed and distributed to students before and after treatment. Data analysis of a paired sample t-test was used in this study with the help of SPSS. Descriptive test results showed differences in pretest and posttest scores. Still, based on hypothesis testing, it was concluded that the puzzle estafet game did not significantly affect the teamwork of elementary school students.